A review of health information systems in Malaysian public hospitals: current practice, benefits, and barriers - Nabihah Ali; Nachia Banu Abdul Rahim; Nelson Lean Leong; Priya Kunasagran; Ramalingam Thulasiraman; Rudi Nasib; Sheila Mujin; Abdul Rahman Ramdzan; Zawiah Mansor; Mohamad Sabri Sinal (Authorea, 2025)
Hospital Information System (HIS) is one of the important pillars in current healthcare system practice worldwide. The study initiated after a review revealed a scarcity of applications and studies on HIS in Malaysia’s public hospital setting. This scoping review aims to explore the current practice, benefits, and barriers associated with Health Information Systems (HIS) in Malaysian public hospitals. Utilizing the PRISMA guidelines, relevant literature was sourced from the SCOPUS database, focusing on publications from 2012 to 2022. A total of nine studies were selected for analysis. The review reveals that, despite being introduced early, the implementation and utilization of HIS in Malaysian public hospitals remain limited and slow. HIS offers substantial benefits, including improved clinical documentation, administrative efficiency, and enhanced quality and coordination of care. However, several barriers hinder its successful implementation, categorized into five main areas: financial, organizational, behavioral, technological, and support-related. Addressing these challenges is essential for realizing the full potential of HIS in improving patient care and hospital efficiency. This review serves as a baseline for identifying critical issues and guiding future improvements in Malaysia’s public healthcare sector.